Solutions of the bound-state Faddeev-Yakubovsky equations in three dimensions by using NN and 3N potential models - Hadizadeh, M. R. [UNESP]; Tomio, Lauro [UNESP]; Bayegan, S. (American Physical Society (APS), 2011)
A recently developed three-dimensional approach (without partial-wave decomposition) is considered to investigate solutions of Faddeev-Yakubovsky integral equations in momentum space for three- and four-body bound states, with the inclusion of three-body forces. In the calculations of the binding energies, spin-dependent nucleon-nucleon (NN) potential models [soft-core potential S3, Malfliet-Tjon (MT) I-III, Yamaguchi-type potentials (YS), and P5.5-model of Gibson-Lehman (P55GL)] are considered along with the scalar two-meson exchange three-body potential. The presently reported results agree well with the ones obtained by other techniques, demonstrating the advantage of an approach in which the formalism is much more simplified and easy to manage for direct computation. © 2011 American Physical Society.